Model kompleksowej oceny działalności inwestycyjnej jednostek gospodarczych - Tomidajewicz, Janusz J. (Wydział Prawa i Administracji UAM, 1979)
Taking advantage of until now existing system of appraisal of investment activities used in Poland, an attempt is undertaken in the article to construct a model ensuring comprehensive appraisal of these activities. Let us assume that the appraisal of imvesttmemt activities on all stages of investment process is based on employment of an effectiveness measure grounded on a comparison of inputs and outputs of investment enterprises. After distinguishing planning, realization and working stages in investment ctivities there are proposed in the model such methods of appraisal of these stages that ensure fulfilment of a condition of conformability of these appraisals among them. They ensure at the same time that division of the whole process into subsequent, separately evaluated stages does not create a possibility of omission in the field of vision activities being disadvantageous from social and economic points of view, such as: unjustified increase in investment and working outlays and unattainability of desired production effects.
On a Model of Comprehensive Appraisal of Investment Activities of Economic Units